(3i-5)(6i+3)

(3i - 5)(6i + 3) Apply complex arithmetic rule: (a+bi)(c+di)=(ac-bd)+(ad+bc)i; a= -5, b = 3, c = 3, d = 6 =(-5 * 3 - 3 * 6) + (-5 * 6 + 3 * 3)i; = -33 + (-21)i; = -33 -21i

Question

Asked 10/21/2013 12:06:44 PM

Updated 320 days ago|9/4/2017 1:51:53 PM

3 Answers/Comments

Rating

3

(3i - 5)(6i + 3)

= 18i^2 + 9i - 30i - 15;

= 18i^2 - 21i - 15

= 18i^2 + 9i - 30i - 15;

= 18i^2 - 21i - 15

Added 320 days ago|9/4/2017 11:51:15 AM

This answer has been flagged as incorrect.

Flagged by jeifunk [9/4/2017 12:36:37 PM]

3

[Deleted]

Added 320 days ago|9/4/2017 1:48:43 PM

This answer has been added to the Weegy Knowledgebase

Deleted by alfred123 [9/4/2017 1:50:54 PM]

3

[Deleted]

Added 320 days ago|9/4/2017 1:51:06 PM

This answer has been added to the Weegy Knowledgebase

Deleted by alfred123 [9/4/2017 1:51:46 PM]

3

(3i - 5)(6i + 3)

Apply complex arithmetic rule: (a+bi)(c+di)=(ac-bd)+(ad+bc)i;

a= -5, b = 3, c = 3, d = 6

=(-5 * 3 - 3 * 6) + (-5 * 6 + 3 * 3)i;

= -33 + (-21)i;

= -33 -21i

Apply complex arithmetic rule: (a+bi)(c+di)=(ac-bd)+(ad+bc)i;

a= -5, b = 3, c = 3, d = 6

=(-5 * 3 - 3 * 6) + (-5 * 6 + 3 * 3)i;

= -33 + (-21)i;

= -33 -21i

Added 320 days ago|9/4/2017 1:51:53 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [9/4/2017 2:12:56 PM]

27,104,501

questions answered

There are no comments.